Contributing factors for intestinal parasitic infection in children: a study of Nepal - Das, Rajesh Kumar; Mahato, Pradip Kumar; Neupane, Prabin (International Journal Of Community Medicine And Public Health, 2019)
Background: Intestinal parasitic diseases are common health problems among children in Nepal. The presence of these diseases is an indication of poor hygienic practices. So our objective is to find out the factors that are responsible to cause such infections in our study population. Methods: This is a cross-sectional study to find the causes of parasitic intestinal infection in children. Stool specimens were collected from children below 15 years and studied by microscopy method to detect the causative organisms of infection. Results: Among the sample size of 305, 154 (50.5%) cases were found microscopically positive for parasitic diseases. Age and sex-wise study did not show the significant relationship (P>0.05) for infection. Entamoeba histolytica and Giardia lamblia had higher prevalence i.e., 18.03% (55/154) and 16.06% (49/154). Likewise, infection was higher in children using untreated water sources and municipal water. Many children with unsanitary habits like not washing hands properly before and after eating meals and after using toilet and nail biting habits developed more positive infection. The relationship in this case was significant (P<0.05). Conclusions: Thus, the contributing factors for intestinal parasitic infection in children are lack of hygienic practices among children. Such habits can cause ingestion of infective parasites in the intestine which eventually causes diseases.